Uji Keefektivan Formula Trichoderma sp. Sediaan Tablet Sebagai Dekompuser Limbah Organik Ampas Sagu Menjadi Biokompos - Umrah Umrah; Muhammad Alwi; Muh. Arsal N. Maddo (Biology Department, Mathematics and natural science, Tadulako University, 2011)
Research entitle of “Bioactive compost from sago waste and chicken manure through bioprocess using Trichoderma sp.” have been conducted during March and July 2011. This research have been done in Biotechnology Laboratory, Science Fakulty of Tadulako University. This aims of this study are to produce bioactive compost from waste of sago pulp and chicken manure through bioprocess Trichoderma sp., also to determine the optimum dose of inoculums of Trichoderma sp.. This study was done experimentally and it was based on a completely randomized design. Result of this study showed that P2 (substrate + 2 tablets inoculum/kg substrate) was the best treatment. Key words: Bioactive compost , sago waste, chicken manure, Trichoderma sp.